2020
DOI: 10.1093/rb/rbz053
|View full text |Cite
|
Sign up to set email alerts
|

The observed difference of macrophage phenotype on different surface roughness of mineralized collagen

Abstract: Biomaterials regulate macrophages and promote regeneration function, which is a new hot pot in tissue engineering and regenerative medicine. The research based on macrophage materials biology has appeared happy future, but related research on regulating macrophages and promoting tissue regeneration is still in its infancy. The surface roughness of biomaterials is one of the important factors affecting macrophage behavior. Previous study also found that the surface roughness of many biomaterials regulating macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 26 publications
0
31
0
Order By: Relevance
“…[88] With regard to the mineralized collagen material (with different roughness from 0.92 to 12 µm), a rougher surface could lead to the polarization of THP-1-derived macrophages toward M1 phenotype in vitro with high secretion levels of inflammatory factors (TNF-α, IL-6), while a smoother surface was able to promote the M2-phenotype polarization. [89] Corporately, when considering the influence of surface roughness on macrophage immune responses, in addition to the wide range of surface roughness to be designed, other parameters such as surface chemistry, charge and wettability may also need to be analyzed together to obtain a comprehensive understanding for suitable biomaterial surface design.…”
Section: Surface Roughnessmentioning
confidence: 99%
“…[88] With regard to the mineralized collagen material (with different roughness from 0.92 to 12 µm), a rougher surface could lead to the polarization of THP-1-derived macrophages toward M1 phenotype in vitro with high secretion levels of inflammatory factors (TNF-α, IL-6), while a smoother surface was able to promote the M2-phenotype polarization. [89] Corporately, when considering the influence of surface roughness on macrophage immune responses, in addition to the wide range of surface roughness to be designed, other parameters such as surface chemistry, charge and wettability may also need to be analyzed together to obtain a comprehensive understanding for suitable biomaterial surface design.…”
Section: Surface Roughnessmentioning
confidence: 99%
“…We demonstrated that the inflammatory and immune responses of macrophages cultured on MC were significantly lower than those cultured on collagen. Our previous study showed that MC modulated the macrophages' cell morphology as well as secretion of cytokines, such as TNF‐a, IL‐6, IL‐4, and IL‐10 in a time‐dependent manner 20 . However, the signaling pathways involved are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, MC induced chemotaxis and differentiation of mesenchymal stem cells into osteoblasts, resulting in natural mineralized matrix and collagen, which further promoted the growth of new bone tissue 16,17 . Several studies have confirmed using both in vitro and in vivo experiments that MC promoted bone regeneration and stimulated osteogenic differentiation 18‐20 . In the recent, more and more experts and scholars have become increasingly recognized the importance of local environment surrounding regenerating tissue, and turned much attention to how the immune system can be manipulated to achieve the purpose of implanted scaffolds, especially in inhibiting foreign body rejection and strengthening the binding of scaffolds to natural tissue 22 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The upregulation of anti-inflammatory factors was observed in cells cultured on the hydrophilic rough surface, suggesting M2 macrophage activation. The significant difference between the FSTi group and the FTi group may be due to the wetting performance; Wettability has a stronger effect than roughness on interleukin secretion, it may not be the only reason for the increase in anti-inflammatory factors [ 67 , 68 ]. Therefore, these surface-specific reactions suggest that chemical effects may lead to unique genotypical responses and to eventual phenotypical responses through properly optimized surface properties that affect macrophage activation.…”
Section: Discussionmentioning
confidence: 99%